Sistem Pakar Deteksi Kesehatan Mental Remaja Akibat Bullying Dengan Pendekatan Algoritma Forward Chaining - Rima Melati; Ranny Meilisa (Fakultas Teknik Universitas Persada Indonesia YAI, 2026)
Bullying is a critical issue among school adolescents that significantly impacts mental health, ranging from stress and anxiety to depression. Data from Riskesdas (2018) recorded that over 19 million Indonesians suffer from emotional mental disorders, while a 2022 survey indicated that more than 95% of adolescents have experienced symptoms of anxiety and depression. This situation highlights the urgency of early detection of mental health issues in bullying victims. This study aims to develop an expert system for detecting adolescent mental health conditions resulting from bullying using the Forward Chaining algorithm. This algorithm was selected for its ability to derive diagnostic conclusions based on the symptom facts experienced by students. A case study was conducted at SMK Jakarta Timur 2, involving students and guidance and counseling teachers as data sources and validators. The research employs an applied research method with a software engineering approach using the Waterfall model. Data were collected through literature review, questionnaires, and interviews, then formulated into IF–THEN rules for the system's knowledge base. The system was tested using black-box testing and validated by experts (guidance teachers/psychologists). The result of this research is an accurate computer-based expert system application, expected to contribute to the field of educational psychology and provide practical benefits for schools in the early detection of the psychological impacts of bullying on adolescents.